Adsorption of fulvic acid onto polyamide 6 microplastics: Influencing factors, kinetics modeling, site energy distribution and interaction mechanisms. (June 2021) - Tang, Shuai; Lin, Lujian; Wang, Xuesong; Sun, Xuan; Yu, Anqi
Abstract: Information on the interactions of microplastics (MPs) with dissolved organic matter (DOM) is essential for understanding their environmental impacts. This study selected fulvic acid (FA) as a typical DOM to investigate the influence of contact time, temperature, dosage, solution pH, salinity, and coexisting metal ions on the adsorption of FA onto polyamide 6 (PA6) MPs. The adsorption kinetic and isotherm can be successfully described by mixed-order (MO) and Freundlich models. The adsorption site energy distribution based on the Freundlich equation was applied to analyze the interaction between FA and PA6-MPs and the adsorption site heterogeneity. Thermodynamic analysis demonstrated that the values of parameters ( Δ G a d s °, Δ S a d s °, Δ H a d s ° ) were significantly affected by initial solution concentrations and the adsorption process was spontaneous, endothermic, and randomness-increased. Fourier transform-infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS) revealed the importance of amide functional groups of PA6-MPs in controlling FA adsorption. Hydrogen bonds, hydrophobic, electrostatic, and n-π electron donor-acceptor (n-π EDA) interactions played different roles on adsorption of FA under different conditions of solution chemistry. These findings are beneficial to provide new insights involving the adsorption behavior and interaction mechanisms of FA onto PA6-MPs for the environmental risk assessment of MPs. Graphical abstract: Image 1 Highlights: FA adsorption was mainly controlled by the step of adsorption on active sites. FA adsorption was affected by pH, salinity, temperature and coexisting metal ions. Solution chemistry led to different contributions of four interaction mechanisms. This study provides new insights for the environmental risk assessment of MPs.